2017
DOI: 10.1248/bpb.b16-00833
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Albumin Secretion and Metabolic Activity of Cytochrome P450 1A1 of Human Hepatoblastoma HepG2 Cells in Multicellular Spheroids by Controlling Spheroid Size

Abstract: Key words albumin; CYP1A1; human hepatoblastoma HepG2 cell; size control; spheroid Three-dimensional multicellular spheroids possess greater in vivo tissue-like morphology and function than two-dimensional monolayered cells. Therefore, multicellular spheroids are considered useful in vitro systems for drug screening, including tests of drug metabolism and toxicity, [1][2][3][4][5][6] and for studying tumor metastasis. 7,8) Furthermore, such spheroids have attracted much attention for application in cell-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 40 publications
5
27
0
Order By: Relevance
“…These albumin concentrations are in agreement with several others studies using HepG2 cells [48][49][50]. CYP3A4 activity (Figure 5b) exhibited a profile inversely proportional to albumin secretion, also in agreement with the literature [51][52][53]. In line with these data, we also observed cytoplasmic expression of albumin in HepG2 cells within both types of scaffolds, and nuclear expression of HNF-4α in most cells at day seven (Figure 5c).…”
Section: Cell Functionality In Porous Scaffoldssupporting
confidence: 93%
See 1 more Smart Citation
“…These albumin concentrations are in agreement with several others studies using HepG2 cells [48][49][50]. CYP3A4 activity (Figure 5b) exhibited a profile inversely proportional to albumin secretion, also in agreement with the literature [51][52][53]. In line with these data, we also observed cytoplasmic expression of albumin in HepG2 cells within both types of scaffolds, and nuclear expression of HNF-4α in most cells at day seven (Figure 5c).…”
Section: Cell Functionality In Porous Scaffoldssupporting
confidence: 93%
“…We found a low CYP3A4 activity of HepG2 constructs in our scaffolds similar to the limited activity observed for small size cell spheroids of less than 200 µm [66]. For larger HepG2 spheroids, hypoxic areas in HepG2 3D constructs increases in the core and subsequently increases CYP3A4 activity [53]. In our study, no hypoxia or cell death was observed in 3D constructs which could explain the reduced activity of CYP3A4 overtime.…”
Section: Discussionsupporting
confidence: 79%
“…HepG2 was originally thought to be a hepatocellular carcinoma cell line and was utilized to investigate hepatocellular carcinoma. However, previous research has shown that HepG2 is a HB-derived cell line (22), which has a crucial role in studying the underlying progression and mechanism of HB (23,24). In the present study, it was confirmed that CXCL5 and its receptor CXCR2 are expressed in HepG2 cells.…”
Section: Discussionsupporting
confidence: 79%
“…The expression levels of AFP and CYP3A4 in 50 µm spheroids were greater than those of the two larger spheroids (Figure d). Consistent with this result, it has been reported that the function of HepG2 cells is better for smaller spheroids than for larger spheroids . In spheroid culture, the upper limit of the viable size is 100–150 µm in diameter due to oxygen depletion .…”
Section: Discussionsupporting
confidence: 77%